Technology of polymer packaging - Ghosh, Arabinda (Hanser Publishers, 2015)
Annotation Aimed at engineering students, engineers, and technologists of the packaging industry, this book provides the essentials of polymer packaging. It provides the reader with the knowledge and skills to identify and solve problems in packaging processes, and thereby develop functional packaging. Sales and marketing people involved in the packaging industry will also find this a valuable resource. A short primer on polymeric materials and additives is followed by descriptions of the most important production processes for polymer packaging - both continuous and discontinuous. Further chapters cover technology of sealing and different converting processes of packaging webs. The clear, practical informational focus stems from the author's extensive experience in the packaging industries and as an educator.
Keywords: Food -- Packaging -- Materials.; Polymers.; elektronické knihy; electronic books